How Contextual Cues Impact Response and Conversion Rates of Online Surveys - Pan, Bing; Woodside, Arch; Meng, Feng (SAGE Publications Inc, 2014)
This study investigates how three contextual cues—researcher identity, sponsor identity, and incentive type—affect response and conversion rates of online conversion surveys. Applying an experimental design via an online survey of information inquirers to a tourist destination, the study demonstrates that researcher identity and sponsor identity affect the response rates, and the specific arrangement can increase the response rate substantially. The three contextual cues do not affect conversion rates significantly